Graphite negative electrode material, negative electrode plate and battery
By using primary particles containing oxygen-containing functional groups and secondary particles of clad elements in graphite negative electrode materials, combined with controlling the particle mass proportion and particle size, the problem of poor battery expansion and thermal abuse performance in fast-charge graphite systems is solved. Graphite negative electrode material with low expansion and high thermal abuse performance is achieved.
Patent Information
- Application Number
- CN202411264767.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-10
AI Technical Summary
In a fast charging graphite system, how to build a graphite negative electrode material with low expansion and excellent thermal abuse performance to solve the problem of poor battery expansion and high temperature performance.
The graphite negative electrode material consisting of primary particles and secondary particles is used, where the surface of primary particles contains oxygen-containing functional groups, and the secondary particle coating layer contains elements such as B, P, N, F, etc. by controlling the particle mass ratio and particle size. Improves the battery's fast charging capability and thermal abuse performance.
Effectively reduce the battery cycle expansion rate, improve high-temperature cycle performance and dynamic performance, ensure fast charging and discharging capabilities, and avoid lithium metal precipitation, improving the battery's fast charging performance.
Smart Images

Figure CN119133405A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a graphite negative electrode material, a negative electrode sheet and a battery. Background Art
[0002] Compared with graphite, amorphous carbon contains abundant micropores and can accommodate more lithium ions. Coating graphite with amorphous carbon can effectively increase the solid-phase diffusion coefficient of graphite and improve the fast-charging ability of the material to a certain extent. Fast-charging graphite usually has a large amount of amorphous carbon coating, but amorphous carbon has many surface defects. When its content is too high, the side reactions of the electrolyte on its surface increase at high temperatures, the cycle expansion is large, and the thermal abuse performance is poor. Therefore, in the fast-charging graphite system, how to construct graphite with low expansion and excellent thermal abuse performance is a difficult problem that needs to be solved in the field of fast-charging negative electrode material development and battery design. Summary of the invention
[0003] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art and to provide a graphite negative electrode material, a negative electrode sheet and a battery. The use of the graphite negative electrode material can ensure the fast charging capability of the battery while improving the thermal abuse performance of the battery and alleviating battery expansion.
[0004] In order to achieve the above-mentioned object, the present invention provides a graphite negative electrode material in a first aspect, wherein the graphite negative electrode material comprises primary particles and secondary particles comprising a coating layer;
[0005] The surface of the primary particle contains oxygen-containing functional groups, the oxygen-containing functional groups include C=O, COO- and CO single-bond functional groups, and the total proportion of C=O functional groups and COO- functional groups in the oxygen-containing functional groups is greater than the proportion of CO single-bond functional groups; the coating layer contains a first element, a second element and a third element, the first element includes at least two of B, P, N, F and S, the second element is a transition metal, and the third element is an alkali metal and / or an alkaline earth metal;
[0006] The graphite negative electrode material satisfies 0.01≤α / m≤0.1 and 0.5≤100*β*η / m≤10;
[0007] Wherein, m is the mass content of carbon element in the graphite negative electrode material, in wt%; α, β and η are the mass contents of the first element, the second element and the third element in the graphite negative electrode material, in wt%;
[0008] 6≤X1d1+X2d2≤12.6; wherein X1 and X2 are the mass contents of secondary particles and primary particles in the graphite negative electrode material, respectively; d1 and d2 are the median particle sizes of secondary particles and primary particles, respectively, in μm.
[0009] A second aspect of the present invention provides a negative electrode sheet, which comprises a negative electrode current collector and a negative electrode active material layer arranged on the surface of the negative electrode current collector, wherein the negative electrode active material layer comprises the graphite negative electrode material described in the first aspect.
[0010] A third aspect of the present invention provides a battery, wherein the battery comprises the graphite negative electrode material described in the first aspect and / or the negative electrode sheet described in the second aspect.
[0011] The present invention adopts the above technical solution to achieve the following beneficial effects:
[0012] The graphite negative electrode material described in the present invention is composed of secondary particles and primary particles, wherein there is a coating layer on the surface of the secondary particles, and the secondary particle coating layer contains a first element, a second element and a third element, and the presence of these elements can improve the fast charging ability of the battery and enhance the stability of the SEI film. There are oxygen-containing functional groups on the surface of the primary particles, and the sum of the C=O and COO- functional groups accounts for more than the CO single-bond functional group, which can improve the compatibility of the material with the electrolyte, effectively reduce the polarization of the battery cycle process, and thus improve the high-temperature cycle performance of the battery, and to a certain extent can improve the kinetic performance of the material. Further coordinated control of the mass ratio and particle size of the secondary particles and the primary particles can effectively improve the thermal abuse performance of the battery, ensure rapid charging and discharging, reduce the cycle expansion rate of the battery, and also improve the kinetic performance of the negative electrode. During the fast charging process of the battery, the precipitation of lithium metal is alleviated or even avoided, and the fast charging performance of the battery is improved.
[0013] The endpoints and any values of the range disclosed in this article are not limited to the precise range or value, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Herein, in the absence of special instructions, data ranges include endpoints. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 Shown is a SEM image of the graphite negative electrode material used in Example 1 of the present invention, wherein the particles in the yellow circle are secondary particles, and the particles in the red circle are primary particles.
[0015] Figure 2 Graphite anode material particle size distribution curve used in Example 1.
[0016] Figure 3 The thermogravimetric curve and thermogravimetric differential curve of the graphite negative electrode material used in Example 1.
[0017] Figure 4This is the XRD curve of the graphite negative electrode material used in Example 1.
[0018] Figure 5 The charge and discharge curves of the button-type half-cell prepared with the graphite negative electrode material used in Example 1.
[0019] Figure 6 This is the X-ray photoelectron spectroscopy (XPS) test result of the primary particles in the graphite negative electrode material used in Example 1. DETAILED DESCRIPTION
[0020] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0021] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.
[0022] A first aspect of the present invention provides a graphite negative electrode material, the graphite negative electrode material comprising primary particles and secondary particles comprising a coating layer;
[0023] The surface of the primary particle contains oxygen-containing functional groups, the oxygen-containing functional groups include C=O, COO- and CO single-bond functional groups, and the total proportion of C=O functional groups and COO- functional groups in the oxygen-containing functional groups is greater than the proportion of CO single-bond functional groups; the coating layer contains a first element, a second element and a third element, the first element includes at least two of B, P, N, F and S, the second element is a transition metal, and the third element is an alkali metal and / or an alkaline earth metal;
[0024] The graphite negative electrode material satisfies 0.01≤α / m≤0.1 and 0.5≤100*β*η / m≤10;
[0025] Wherein, m is the mass content of carbon element in the graphite negative electrode material, in wt%; α, β and η are the mass contents of the first element, the second element and the third element in the graphite negative electrode material, in wt%;
[0026] 6≤X1d1+X2d2≤12.6; wherein X1 and X2 are the mass contents of the secondary particles and the primary particles in the graphite negative electrode material, respectively; d1 and d2 are the median particle sizes of the secondary particles and the primary particles, respectively, in μm. The coating layer of the secondary particles contains the first element, the second element and the third element, the presence of which can improve the fast charging capability of the battery and enhance the stability of the SEI film; there are oxygen-containing functional groups on the surface of the primary particles, and the sum of the C=O and COO- functional groups accounts for a greater proportion than the CO single-bond functional group, which can improve the compatibility of the material with the electrolyte, effectively reduce the polarization of the battery cycle process, and thus improve the high-temperature cycle performance of the battery, and to a certain extent, can improve the kinetic performance of the material. Further coordinated control of the mass proportion and particle size of the secondary particles and the primary particles can effectively improve the thermal abuse performance of the battery, ensure rapid charging and discharging, reduce the cycle expansion rate of the battery, and improve the kinetic performance of the negative electrode. During the fast charging process of the battery, the precipitation of lithium metal is alleviated or even avoided, and the fast charging performance of the battery is improved.
[0027] In the present invention, "primary particles" and "secondary particles" have the conventional meanings in the art. "Primary particles" refer to the initial particles formed during the processing of graphite raw materials; "secondary particles" are formed by processing the primary graphite particles again, and refer to particles formed by the aggregation of several primary particles. Figure 1 The figure shows an exemplary SEM image of the graphite negative electrode material of the present invention, wherein the particles in the yellow circle are secondary particles, and the particles in the red circle are primary particles. It can be found that the secondary particles are obviously bonded together to form a multi-layer structure, while the primary particles are dispersed single particles. In the present invention, the secondary particles may not be prepared from the primary particles, that is, the primary particles and the secondary particles in the present invention may not have continuity in the preparation process.
[0028] The primary particles can be obtained by gas-phase modification of the graphitized material under an oxygen-containing atmosphere, so that the ratio of different functional groups on the surface of the primary particles changes, and contain oxygen-containing functional groups. The presence of oxygen-containing functional groups can improve the compatibility of the material with the electrolyte, effectively reduce the polarization of the battery cycle process, and thus improve the high-temperature cycle performance of the battery, and to a certain extent can improve the kinetic properties of the material. The graphitized material can be obtained by graphitizing a carbon-based raw material. The method and conditions of the graphitization treatment and the carbon-based raw material used can be conventional choices in the art. For example, the carbon-based raw material can be needle coke, asphalt coke, ordinary petroleum coke, anthracite coke, etc.; the conditions of the graphitization treatment can include: a temperature of 2500-4000°C and a time of 4-12h.
[0029] In some embodiments, the secondary particles can be obtained by coating a graphitized material and then carbonizing it. The specific operation mode, conditions and the amount of each component can be selected according to the situation. The coating agent used in the coating can be obtained by mixing carbon-containing materials such as asphalt, liquid phase resin and biomass carbon. The asphalt can be petroleum asphalt and / or coal asphalt. The liquid phase resin and biomass carbon can be one or more of phenolic resin, starch, sucrose, etc.; one or more additives are added during the coating, and the additives contain a first element, a second element and a third element, and the amount of the additives is selected according to the needs. The conditions for the carbonization treatment may include: a temperature of 800-1600°C and a time of 4-12h.
[0030] In the present invention, the method for testing the functional groups on the surface of primary particles is as follows: disassembling the battery to obtain the negative electrode sheet, soaking and cleaning it with DMC and then drying it, removing the copper foil to obtain the negative electrode active material layer powder, and using the XPS method to test the functional groups of the primary particles in the negative electrode powder.
[0031] In some embodiments, in the graphite negative electrode material, the mass content of O element in the primary particles is 5wt%-7wt%, such as 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%. The primary particles may also contain at least one of B, P, N, F and S.
[0032] In the secondary particle coating layer, when the first element satisfies 0.01≤α / m≤0.1, it can effectively improve the compatibility of the material and the electrolyte contact interface and provide certain active sites, which is beneficial to improving the fast charging ability of the battery; when α / m<0.01, the first element content is too little, the battery impedance increases, and the battery charging capacity decreases, which easily leads to lithium precipitation during the fast charging and discharging process; when α / m>0.1, the first element content is too much, the side reaction between the material and the electrolyte increases, resulting in poor thermal abuse performance of the battery and poor high temperature cycle retention rate. The second element and the third element meet 0.5≤100*β*η / m≤10, which can effectively reduce the kinetic energy barrier of the desolvation process, reduce the resistance of lithium ion embedding into the negative electrode, and improve the compatibility of the material and the electrolyte, which is beneficial to generate a stable SEI interface, reduce the polarization of the battery, and then reduce the occurrence of side reactions and improve the thermal abuse performance of the battery. If 100*β*η / m<0.5, the content of the second element and the third element is too low, and the improvement on battery performance is limited; if 100*β*η / m>10, the content of the second element and the third element is too high, and the content of inactive components of the material is too high, resulting in a decrease in the material's gram capacity, reducing the energy density of the battery, and at the same time resulting in fewer active sites on the surface of the granular material, reducing the battery's fast charging capability, causing the battery to easily precipitate lithium during fast charging and attenuate cycle performance.
[0033] In some embodiments, m≥75, for example, it can be 75, 80, 85, 90, 92, 94, or 96.
[0034] In some embodiments, 0<α≤9, for example, it can be 0.1, 1, 3, 5, 7, 9. The first element includes F and S. Preferably, in the graphite negative electrode material, the content of F is 5wt% or less, for example, it can be 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, and the content of S is 4wt% or less, for example, it can be 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%.
[0035] In some embodiments, 0<β≤4, for example, it can be 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4.
[0036] In some embodiments, the second element includes at least one of Ti, Mn, Fe, Co, Ni, and Cr, and in some embodiments, includes Ti.
[0037] In some embodiments, 0<η≤3, for example, it can be 0.1, 0.5, 1, 1.5, 2, 2.5, 3.
[0038] In some embodiments, the third element includes at least one of Li, Ca, and Na, and in some embodiments, includes Ca.
[0039] The testing method for the first element, the second element and the third element is as follows: the battery is disassembled to obtain the negative electrode sheet, which is then soaked and cleaned with DMC and dried, and the copper foil is removed to obtain the negative electrode active material layer powder. The content of the first element in the powder is obtained by EDS testing, and the content of the second and third elements in the powder is obtained by ICP testing.
[0040] In the present invention, 6≤X1d1+X2d2≤12.6, for example, it can be 6, 7, 8, 9, 10, 11, 12, 12.6. When the following conditions are met, the added mass proportion and particle size of the secondary particles and primary particles are controlled at the same time to avoid excessive or insufficient mass proportion of the primary particles, and to avoid excessive or small particle sizes of the secondary particles and the primary particles, thereby improving the thermal abuse performance and cyclic expansion of the battery, while ensuring the fast charging capability of the battery.
[0041] In some embodiments, X1≥X2. In some embodiments, 50%≤X1≤80%, for example, it can be 50%, 55%, 60%, 65%, 70%, 75%, 80%.
[0042] In some embodiments, 20%≤X2≤50%, for example, it can be 20%, 25%, 30%, 35%, 40%, 45%, or 50%.
[0043] In some embodiments, 0.16≤X1X2 / (X1+X2)≤0.25, for example, it can be 0.16, 0.18, 0.2, 0.22, 0.24, 0.25. When X1 and X2 satisfy the above relationship, the proportion of the amount of primary particles added can be controlled within the preferred range, which is beneficial to improving the thermal abuse performance of the battery. At the same time, due to the combination of primary particles and secondary particles, the rebound rate and porosity of the pole piece can be increased to a certain extent, which is beneficial to improve the seepage capacity of the electrolyte and the migration rate of ions, improve the fast charging capacity of the battery, and reserve a certain space for the cyclic expansion of the battery, which is beneficial to reduce the expansion rate of the battery during the cycle. If the proportion of X2 is too large, that is, the proportion of primary particles is too large, since there is no coating on the surface of the primary particles, there are relatively few lithium insertion channels, which leads to increased battery impedance, poor dynamics, poor charging capacity, large battery polarization, and easy lithium precipitation under high-rate charging conditions, resulting in large expansion, so it is necessary to prevent the addition of too many primary particles from causing poor dynamics, poor charging capacity and large expansion. If the proportion of X2 is too small, the proportion of primary particles is too small, the secondary particles are more, and the amount of coating layer relative to the total active material is too large. Since the coating layer is amorphous carbon, there are many defects inside the carbon layer, and the side reactions between the electrolyte and the material increase at high temperatures, the temperature rise inside the battery is large, resulting in the battery's thermal abuse performance not being improved. In addition, if there are too many secondary particles, the rebound of the negative electrode sheet is too low, resulting in a decrease in the electrode sheet porosity and a worse constant current charging ratio of the battery cell.
[0044] In some embodiments, d1>d2. In some embodiments, d1 is 8-14, such as 8, 9, 10, 11, 12, 13, 14. In some embodiments, d2 is 6-12, such as 6, 7, 8, 9, 10, 11, 12. Through research, it is found that secondary particles of a certain particle size are matched with gas-phase modified primary particles of a certain particle size, which can effectively provide a buffer space for the expansion of secondary particles during the charge and discharge process and improve the thermal abuse performance of the battery. If d1 is too large, the cyclic expansion of the secondary particles cannot be suppressed, and the internal resistance increases, and the cyclic expansion is large. If d1 is too small, it cannot serve as a bridge between secondary particles. The effect of increasing porosity and increasing lithium insertion paths is poor, the specific surface area of the material increases, the side reactions inside the battery cell increase, the thermal abuse performance decreases, and it is easy to cause large polarization of the battery cell during the cycle process, resulting in a rapid attenuation of the battery cycle retention rate; if d2 is too large, the internal resistance increases, and the charging capacity deteriorates. If d2 is too small, it cannot provide support for the secondary particles. The supporting role here can be understood as the primary particles are built between the secondary particles. On the one hand, it can prevent the OI value of the electrode from being too small (the isotropy of the secondary particles makes the OI value of the electrode small, and the anisotropy of the primary particles makes the OI value of the electrode large. The addition of primary particles increases the OI value of the electrode to a certain extent), and increase the rebound rate and porosity of the electrode; on the other hand, it makes a certain gap between the particles, which is conducive to improving the seepage capacity of the electrolyte and the migration rate of ions, increasing a certain lithium insertion path, and ensuring the rapid charging and discharging capability of the battery cell.
[0045] The median particle size of the secondary particles and the primary particles is tested using a laser particle size analyzer, and the median particle size based on the volume density distribution is the median particle size of the negative electrode material.
[0046] In some embodiments, the mass content of the coating layer in the graphite negative electrode material is W, and satisfies 0.4%≤W≤2.5%. The coating layer refers to the one obtained by mixing the primary particles with carbon-containing materials such as asphalt, liquid phase resin and biomass carbon. The asphalt may be petroleum asphalt or coal asphalt. The physical properties of the asphalt are generally: the softening point is 180-220°C, and the coking value is 50%-60%. The liquid phase resin and biomass carbon may be one or more of phenolic resin, starch, sucrose, etc. When W<0.4%, the amount of the coating layer is too small, the lithium insertion channel on the surface of the material is reduced, the material impedance becomes larger, and the dynamics is insufficient; when W>2.5%, the amount of the coating layer is too much. Since the coating layer belongs to amorphous carbon, there are many defects inside the carbon layer, which leads to an increase in side reactions with the electrolyte, and the internal temperature rise of the battery is too high at high temperature, the battery is prone to ignition, and the thermal abuse performance is reduced. Therefore, an appropriate amount of coating layer is beneficial to ensure the material dynamics while improving the thermal abuse performance of the battery.
[0047] Test method for the amount of coating layer of graphite negative electrode material: disassemble the battery, obtain the negative electrode sheet, soak and clean it with DMC, dry it, then clean it with deionized water, pour off the supernatant and remove the copper foil, dry it to obtain the negative electrode active material layer powder, weigh the powder weight w1, place the negative electrode active material layer powder in an air atmosphere, heat it to 500℃ at 10℃ / min and keep it for 2h, and record the weight of the powder after calcination w2. The amount of coating layer W = (w1-w2)-w1×n, n is the proportion of the conductive agent added to the negative electrode when preparing the negative electrode sheet, and the conductive agent is at least one of carbon black, acetylene black, carbon nanotubes, and graphene. Because the coating layer belongs to disordered carbon and has many lattice defects, it will be preferentially oxidized to CO2 and volatilize under high temperature conditions, while the graphite lattice is complete and orderly, and it is difficult to be oxidized and volatilized in a short time.
[0048] In some embodiments, d is the median particle size of the graphite negative electrode material, in μm, 8≤d≤13, for example, 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, 12, 12.5, 13. In one embodiment, the particle size volume distribution of the graphite (i.e., the graphite negative electrode material) after the secondary particles and the primary particles are mixed is as follows: Figure 2 shown.
[0049] Testing method for the median particle size of negative electrode materials: disassemble the battery to obtain the negative electrode sheet, soak and clean it with DMC and then dry it, then wash it with deionized water, pour off the supernatant and remove the copper foil, and dry it to obtain the negative electrode active material layer powder. Place the negative electrode active material layer powder in an argon atmosphere, heat it to 400°C at 10°C / min and maintain it for 2h, cool it down and use a laser particle size analyzer to test it, and the median particle size based on the volume density distribution is the median particle size of the negative electrode material.
[0050] In some embodiments, the thermogravimetric curve of the negative electrode material shows that the weight of the material is substantially unchanged relative to the initial weight at 700°C, and the thermogravimetric differential curve has a weight gain peak between 300°C and 600°C and at least one weight loss peak in a temperature range below the weight gain peak, such as Figure 3 shown.
[0051] In some embodiments, in a button half-cell test, the capacity of the graphite negative electrode material when delithiation is to 0.3V is q1, the capacity when delithiation is to 0.85V is q2, and the capacity when delithiation is to 1.5V is q3, all in units of mA·h, and q1, q2 and q3 satisfy 0.04<(q3-q2) / (q3-q1)<0.3.
[0052] Button half-cell test method: (1) Graphite negative electrode material, Super P, sodium carboxymethyl cellulose, and styrene-butadiene rubber are mixed in a mass ratio of 93.5:1.0:1.5:4.0, deionized water is added, and the mixture is mixed evenly under the action of a vacuum mixer to obtain a negative electrode slurry; (2) The negative electrode slurry in step (1) is coated on a copper foil, dried in an oven at 80°C, and then transferred to a vacuum oven at 100°C and dried for 12 hours to obtain a surface density of about 6.0 mg / cm 2 In a dry environment, the negative electrode sheet in step (2) is about 1.3g / cm 3 The compaction density is rolled and then a negative electrode disc with a diameter of 12 mm is formed by a punching machine; (4) in a glove box, the negative electrode disc in step (3) is used as a working electrode, a metal lithium sheet is used as a counter electrode, a polyethylene diaphragm with a thickness of 20 μm is used as an isolation membrane, an electrolyte is added, and a button-type half-cell is assembled; the electrolyte can be a mixed solution with a mass ratio of EC:PC:PP:LiPF6:FEC:PS=13:13:50:15:5:4. (5) Using a LAND test system, the button half-cell in step (4) was tested by inserting lithium to 0.005 V at a current of 0.1 mA to obtain a lithium insertion capacity of 1, allowing the battery to stand for 10 min, inserting lithium to 0.005 V at a current of 0.05 mA to obtain a lithium insertion capacity of 2, allowing the battery to stand for 10 min, and then removing lithium to 1.5 V at a current of 0.1 mA to obtain a first lithium removal capacity. The sum of the lithium insertion capacity 1 and the lithium insertion capacity 2 is the first lithium insertion capacity. The first lithium removal capacity is calculated by adding the lithium insertion capacity 1 to the lithium insertion capacity 2. The capacity is divided by the mass of the negative electrode material in the above-mentioned negative electrode disc to obtain the gram capacity of the negative electrode material, and the first efficiency of the negative electrode material is obtained by dividing the first lithium removal capacity by the first lithium insertion capacity; (6) The lithium insertion and lithium removal procedures of step (5) are cycled twice, and the second cycle data are taken to obtain the lithium insertion and lithium removal curves of the negative electrode material. During the second lithium removal, the capacity when lithium is removed to 0.3V is q1, the capacity when lithium is removed to 0.85V is q2, and the capacity when lithium is removed to 1.5V is q3.
[0053] A second aspect of the present invention provides a negative electrode sheet, which comprises a negative electrode current collector and a negative electrode active material layer arranged on the surface of the negative electrode current collector, wherein the negative electrode active material layer comprises the graphite negative electrode material described in the first aspect.
[0054] The negative electrode current collector may be a conventional material in the art, such as copper foil, a three-dimensional negative electrode current collector, etc. (such as foam copper, etc.).
[0055] In some embodiments, the negative electrode active material layer further includes a binder and a conductive agent.
[0056] In some embodiments, in the negative electrode active material layer, the content of graphite negative electrode material is 95wt%-99wt%, for example, 95wt%, 96wt%, 97wt%, 98wt% or 99wt%, the content of binder is 0.5wt%-2.5wt%, for example, 0.5wt%, 0.8wt%, 1.2wt%, 1.6wt%, 2wt%, 2.5wt%, and the content of conductive agent is 0.5-2.5wt%, for example, 0.5wt%, 0.8wt%, 1.2wt%, 1.6wt%, 2wt%, 2.5wt%.
[0057] In some embodiments, the binder comprises at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, polyimide, polyamideimide, carboxymethyl cellulose, styrene-butadiene rubber, and polyvinylidene fluoride.
[0058] In some embodiments, the conductive agent comprises at least one of conductive carbon black, carbon nanotubes, carbon fibers, and Ketjen black.
[0059] In some embodiments, the full charge extension rate of the negative electrode sheet is satisfy like If the negative electrode is extended too much, the appearance of the battery may be easily deformed.
[0060] Pole elongation test method: After fully charging the battery, disassemble it and use a 2.5D width tester to test the width of the front, middle and back of the negative electrode of the disassembled battery. Take the average value and the measured value is m. The width of the negative electrode before winding is n, then the elongation of the negative electrode is
[0061] In some embodiments, when the compaction density of the negative electrode sheet is 1.73 g / cm 3 When the OI value of the negative electrode is and In some embodiments, the negative electrode sheet satisfies like If the OI value of the electrode is too small, the electrode will have low rebound and low porosity, which may easily lead to excessive expansion during the cycle and excessive extension of the electrode, which will cause the bottom of the battery membrane to warp. If the OI value of the electrode is too large and the electrode rebound is too large, it will easily lead to a larger initial thickness of the new battery, large polarization during the cycle, and the expansion during the cycle may not be suppressed.
[0062] Test method for the OI value of the electrode: disassemble the battery, obtain the negative electrode, dry it at room temperature, and use an X-ray diffractometer to test the X-ray diffraction pattern of the negative electrode. The diffraction angle 2θ is used as the horizontal axis, the height of the diffraction peak of the {004} crystal plane in the range of 53.7°-55.7° is I1, and the height of the diffraction peak of the {110} crystal plane in the range of 76.4°-78.4° is I2. I1 / I2 is the OI value of the negative electrode.
[0063] A third aspect of the present invention provides a battery, wherein the battery comprises the graphite negative electrode material described in the first aspect and / or the negative electrode sheet described in the second aspect.
[0064] In some embodiments, the battery is a lithium-ion battery. The lithium-ion battery may include a negative electrode sheet, a positive electrode sheet, a separator, an electrolyte, and a housing. The separator is located between the negative electrode sheet and the positive electrode sheet.
[0065] In some embodiments, the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector. The positive electrode active material layer comprises a positive electrode active material, a binder and a conductive agent. The types of the binder and the conductive agent can refer to the types of the binder and the conductive agent in the negative electrode sheet, respectively, and they can be the same or different.
[0066] In some embodiments, the positive electrode active material includes one or more of lithium cobalt oxide (LCO), lithium iron phosphate (LFP), lithium iron manganese phosphate, lithium manganese oxide, lithium nickel oxide, lithium nickel manganese oxide (LNMO), ternary materials (such as nickel cobalt aluminum ternary materials (NCA), nickel cobalt manganese ternary materials (NCM)), lithium nickel cobalt manganese aluminum oxide (NCMA) and lithium-rich manganese-based materials (LRM).
[0067] In some embodiments, in the positive electrode active material layer, the content of the positive electrode active material is 94wt%-98.5wt%, for example, 94wt%, 95wt%, 96wt%, 97wt%, 98wt% or 98.5wt%, the content of the positive electrode binder is 0.7wt%-5wt%, for example, 0.7wt%, 1wt%, 2wt%, 3wt%, 4wt% or 5wt%, and the content of the positive electrode conductor is 0.8wt%-5wt%, for example, 0.8wt%, 1wt%, 2wt%, 3wt%, 4wt% or 5wt%.
[0068] In some embodiments, the electrolyte includes a non-aqueous solvent and a lithium salt; the non-aqueous solvent includes one or more of ethylene carbonate (EC), propylene carbonate (PC), propyl propionate (PP), diethyl carbonate (DEC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC); the lithium salt includes one or more of LiPF6, LiBF4, LiSbF6, LiClO4, LiCF3SO3, LiAlO4, LiAlCl4, Li(CF3SO2)2N, LiBOB and LiDFOB.
[0069] The electrolyte may further include additives, such as 1,3-propane sultone (PS), fluoroethylene carbonate (FEC), and the like.
[0070] In some embodiments, the diaphragm includes a base film, a ceramic layer located on one or both surfaces of the base film, and a polymer layer located on one or both outer sides of the diaphragm.
[0071] In some embodiments, the base film has a thickness of 3 μm-10 μm. In some embodiments, the single-sided ceramic layer has a thickness of 1 μm-5 μm. In some embodiments, the single-sided polymer layer has an average thickness of 50 nm-5 μm.
[0072] In some embodiments, the base film is made of polyolefin, more preferably polypropylene and / or polyethylene. This material gives the separator basic mechanical strength and shape retention ability, and the thermal stability and chemical stability of the base film are also key to ensuring battery safety performance. The uniformity and pore structure of the base film have an important influence on the internal resistance and ion transport performance of the battery.
[0073] In some embodiments, the ceramic layer comprises inorganic particles comprising at least one of the following substances coated with or not coated with carbon: aluminum oxide, barium sulfate, silicon dioxide, silicon monoxide, zirconium oxide, magnesium oxide, vanadium oxide, titanium oxide, boehmite, lithium iron manganese phosphate, and lithium titanate.
[0074] In some embodiments, the polymer layer is made of polyvinylidene fluoride (PVDF) and / or polymethacrylate (PMMA).
[0075] If there is no special explanation, other options of the lithium battery are conventional options in the art. The battery can be assembled in a conventional manner in the art.
[0076] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0077] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0078] The present invention is described in detail below in conjunction with specific embodiments, which are used to understand but not to limit the present invention.
[0079] Preparation Example
[0080] This preparation example is used to illustrate the preparation method of primary particles and secondary particles.
[0081] (1) Preparation of primary particles
[0082] The needle coke is crushed to obtain needle coke powder. The needle coke powder is graphitized in a crucible furnace at a temperature of 3200°C for 8 hours to obtain a graphitized material, wherein the oxygen content is in the range of 3%-4%. An X-ray photoelectron spectroscopy (XPS) test is performed on it, and the results show that the surface of the primary particles contains oxygen-containing functional groups, and the oxygen-containing functional groups are C=O, COO- and CO single-bond functional groups, and the total proportion of C=O functional groups and COO- functional groups in the oxygen-containing functional groups is less than the proportion of CO single-bond functional groups.
[0083] The graphitized material is subjected to gas phase modification treatment in an air atmosphere at a treatment temperature of 500°C. The gas phase modified material is then processed into finished products to obtain primary particles, wherein the Dv50 of the primary particles of artificial graphite is in the range of 6μm-13μm and the specific surface area is 1m 2 / g-2m 2 / g, the discharge capacity is 352-357mAh / g, and the oxygen content is in the range of 5%-7%.
[0084] The primary particles were subjected to an X-ray photoelectron spectroscopy (XPS) test, and the results showed that the primary particles contained oxygen-containing functional groups on their surfaces, wherein the oxygen-containing functional groups were C=O, COO-, and CO single-bond functional groups, and the total proportion of C=O functional groups and COO- functional groups in the oxygen-containing functional groups was greater than the proportion of CO single-bond functional groups, for example Figure 6 By comparison, it is found that compared with the material after graphitization, the proportion of CO single bond functional groups in the primary particles is reduced, while the proportions of C=O functional groups and COO- functional groups are increased.
[0085] (2) Preparation of secondary particles
[0086] The needle coke is crushed to obtain needle coke powder. The needle coke powder is graphitized in a crucible furnace at a temperature of 3200°C for 8 hours to obtain a graphitized material. The primary graphite particles after graphitization are coated and granulated. The equipment used is a vertical coating kettle. The coating agent is modified high-temperature asphalt. One or more additives are added during the coating process. The additives contain a first element, a second element, and a third element. The amount of the additive is selected as needed. Finally, the coated granulated material is carbonized. After adding the additives, by controlling the carbonization temperature and the carbonization time, the particle coating layer can contain the first element, the second element, and the third element. The carbonization temperature is 1100°C and the carbonization time is 8 hours.
[0087] The carbonized material is processed into a finished product to obtain surface-modified secondary particles, wherein the Dv50 of the secondary particles is 8 μm-14 μm and the specific surface area is 1.0 m 2 / g-1.8m 2 / g, and the discharge capacity is 354mAh / g-360mAh / g.
[0088] Example 1
[0089] 1) Preparation of graphite negative electrode materials
[0090] The secondary particles prepared in Preparation Example 1 were mixed with primary graphite particles in a mass ratio of 7:3 to obtain a graphite negative electrode material, wherein the particle size, proportion and content of each component of the secondary particles and primary particles are shown in Table 1. Specifically, in Table 1, m, α, β, η and W are the mass contents of the C element, the first element (F and S), the second element (Ti), the third element (Ca) and the coating layer in the graphite negative electrode material, respectively, in units of wt%. X1 and X2 are the mass contents of the secondary particles and the primary particles in the graphite negative electrode material, respectively; d1, d2 and d are the median particle sizes of the secondary particles, the primary particles and the graphite negative electrode material, respectively, in units of μm. K1 = α / m; K2 = 100*β*η / m; K3 = X1d1+X2d2.
[0091] Figure 1 It is a SEM picture of the graphite negative electrode material, wherein the particles in the yellow circle are secondary particles, and the particles in the red circle are primary particles. It can be found that the secondary particles are obviously bonded together to form a multi-layer structure, while the primary particles are dispersed single particles. Figure 2 is the particle size volume distribution curve of the graphite negative electrode material. Figure 3 The thermogravimetric curve and thermogravimetric differential curve of the graphite negative electrode material show that the material has almost no weight loss after the thermogravimetric test. Figure 4is the XRD curve of the graphite negative electrode material. It can be seen from the figure that the negative electrode material exhibits the crystal diffraction characteristics of graphite, indicating that it retains the basic structure of artificial graphite, thereby ensuring the structural stability of the negative electrode material. Figure 6 Shown are the X-ray photoelectron spectroscopy (XPS) test results of the primary particles, which show that the surface of the primary particles contains oxygen-containing functional groups, which are C=O, COO- and CO single-bond functional groups, with contents of 38%, 26% and 37%, respectively. That is, the total proportion of C=O functional groups and COO- functional groups in the oxygen-containing functional groups is greater than the proportion of CO single-bond functional groups.
[0092] In the button half-cell test, the capacity of the graphite negative electrode material when de-lithiated to 0.3V is q1, the capacity when de-lithiated to 0.85V is q2, and the capacity when de-lithiated to 1.5V is q3, all in units of mA·h. The button half-cell test method is as follows: (1) The graphite negative electrode material, Super P, sodium carboxymethyl cellulose, and styrene-butadiene rubber are mixed in a mass ratio of 93.5:1.0:1.5:4.0, deionized water is added, and the mixture is mixed evenly under the action of a vacuum mixer to obtain a negative electrode slurry; (2) The negative electrode slurry in step (1) is coated on a copper foil, dried in an oven at 80°C, and then transferred to 100°C and dried in a vacuum oven for 12 hours to obtain a surface density of about 6.0 mg / cm 2 In a dry environment, the negative electrode sheet in step (2) is about 1.3g / cm 3 The compaction density is rolled and then a negative electrode disc with a diameter of 12 mm is formed by a punching machine; (4) in a glove box, the negative electrode disc in step (3) is used as a working electrode, a metal lithium sheet is used as a counter electrode, a polyethylene diaphragm with a thickness of 20 μm is used as an isolation membrane, an electrolyte is added, and a button-type half-cell is assembled; the electrolyte can be a mixed solution with a mass ratio of EC:PC:PP:LiPF6:FEC:PS=13:13:50:15:5:4. Figure 5The charge and discharge curve of the button-type half-cell prepared from the graphite negative electrode material. (5) Using the LAND test system, test the button-type half-cell in step (4), insert lithium to 0.005V with a current of 0.1mA to obtain a lithium insertion capacity of 1, let it stand for 10 minutes, insert lithium to 0.005V with a current of 0.05mA to obtain a lithium insertion capacity of 2, let it stand for 10 minutes, and then remove lithium to 1.5V with a current of 0.1mA to obtain the first lithium removal capacity. The sum of the lithium insertion capacity 1 and the lithium insertion capacity 2 is the first lithium insertion capacity. The first lithium removal capacity is obtained. The capacity is divided by the mass of the negative electrode material in the negative electrode disc to obtain the gram capacity of the negative electrode material, and the first lithium removal capacity is divided by the first lithium insertion capacity to obtain the first efficiency of the negative electrode material; (6) The lithium insertion and lithium removal procedures of step (5) are cycled twice, and the second cycle data is taken to obtain the lithium insertion and lithium removal curves of the negative electrode material. In the second lithium removal, the capacity when lithium is removed to 0.3V is q1, the capacity when lithium is removed to 0.85V is q2, and the capacity when lithium is removed to 1.5V is q3. K4 = (q3-q2) / (q3-q1), see Table 1 for details.
[0093] 2) Preparation of negative electrode
[0094] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer. The negative electrode current collector is copper foil with a thickness of 5 μm. The negative electrode active material layer contains the graphite negative electrode material in step (1), conductive carbon black, sodium carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 96.9:0.5:1.3:1.3, and the surface density of the negative electrode active material layer is 6.5 mg / cm 2 The compaction density of the negative electrode is 1.73g / cm 3 , the OI value of the negative electrode sheet under the compaction density is 21, The specific values are shown in Table 1.
[0095] 3) Preparation of positive electrode
[0096] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer. The positive electrode current collector is aluminum foil with a thickness of 10 μm. The positive electrode active material layer contains lithium cobalt oxide, carbon black, carbon nanotubes, and polyvinylidene fluoride in a mass ratio of 97.6:0.9:0.45:1.05, and the surface density of the positive electrode active material layer is 12.0 mg / cm 2 The compaction density of the positive electrode is 4.15g / cm 3 .
[0097] 4) Preparation of diaphragm
[0098] The separator includes a polyethylene layer and a boehmite layer coated on one side of the polyethylene layer, and a polyvinylidene fluoride layer coated on the outside of the polyethylene layer and the boehmite layer. The polyethylene layer is 5 μm thick; the boehmite layer is 2 μm thick and is close to the positive electrode; and the polyvinylidene fluoride layer is 2 μm thick.
[0099] 5) Preparation of batteries
[0100] The positive electrode sheet, the separator and the negative electrode sheet are wound into a battery cell, and then the battery cell is immersed in an electrolyte, encapsulated in an aluminum-plastic film, and assembled into a battery. The electrolyte includes a solvent (EC, PC and EMC with a mass ratio of 1:1:1), a lithium salt and an additive, the lithium salt is LiPF6 with a concentration of 1 mol / L, and the additive includes FEC and PS (1,3-propane sultone) with contents of 7wt% and 3wt%, respectively.
[0101] After formation, pre-cycling, secondary sealing and sorting, the battery thickness at 50% charge is taken as the initial thickness, the battery length is 78mm, the width is 64mm, and the initial thickness is 5.4mm. It has been determined that the full charge elongation rate of the negative electrode sheet of the fresh battery disassembled test is 0.24%.
[0102] Example 2 and Comparative Example 1
[0103] The operation was carried out according to the method described in Example 1, except that the contents of the first element, the second element and the third element in the graphite negative electrode material used were different, as shown in Table 1.
[0104] Comparative Example 2
[0105] Comparative Examples 2-1 to Comparative Examples 2-3 are operated according to the methods of Comparative Examples 1-1 and 1-2 and Example 1, respectively, except that the primary particles used are not subjected to gas phase modification treatment, that is, the primary particles are replaced by graphitized materials, and the graphitized materials are subjected to X-ray photoelectron spectroscopy (XPS) test. The results show that the contents of C=O, COO- and CO single-bond functional groups are 26%, 17% and 57%, respectively, that is, the total proportion of C=O functional groups and COO- functional groups in the oxygen-containing functional groups is less than the proportion of CO single-bond functional groups.
[0106] After measurement, the values of K4 are 0.034, 0.056 and 0.075 respectively.
[0107] Example 3 and Comparative Example 3
[0108] The operation was performed according to the method described in Example 1, except that the mass proportions of the primary particles and the secondary particles were different, as shown in Table 1.
[0109] Example 4 and Comparative Example 4
[0110] The method described in Example 1 was followed, except that the particle sizes of the primary particles and the secondary particles were different from those in Example 1, as shown in Table 1.
[0111] Table 1
[0112]
[0113]
[0114] Note: "*" indicates the same as Example 1, and "#" indicates not measured.
[0115] Example 5 Group
[0116] The operation was carried out in accordance with the method described in Example 1, except that the types of the first element, the second element and the third element added to the secondary particles in the graphite negative electrode material used were different, as shown in Table 2.
[0117] Comparative Example 5
[0118] The method described in Example 1 is followed, except that the secondary particles in the graphite negative electrode material used lack at least one of the first element, the second element and the third element, as shown in Table 2.
[0119] Table 2
[0120] serial number Type and content of the first element Type and content of the second element Type and content of the third element Example 1 3.6wt%F+2.2wt%S 2.5wt%Ti 1.1wt%Ca Example 5-1 3.6wt%N+2.2wt%S * * Example 5-2 3.6wt%F+2.2wt%P 2.5wt%Ni * Example 5-3 * 2.5wt%Ni 1.1wt%Na Comparative Example 5-1 / * * Comparative Example 5-2 * / * Comparative Example 5-3 * * / Comparative Example 5-4 / / /
[0121] Note: “*” indicates the same as Example 1, and “ / ” indicates that the component is not contained or the content of the component is almost negligible.
[0122] Test Case
[0123] The electrochemical performance of the batteries prepared in the examples and comparative examples was tested in the following manner.
[0124] (1) Battery expansion rate: Take the thickness of a fresh battery (50% SOC) as the initial thickness. After the battery is cycled 500 times at 45°C, the thickness of the battery in a fully charged state minus the initial thickness is divided by the initial thickness to obtain the battery volume expansion rate data.
[0125] (2) Thermal abuse performance: Place a fully charged battery in an oven, raise the oven temperature to 135°C, and keep it warm for 60 minutes. After the test, check the battery status. If the battery appearance is normal, it means that the thermal abuse performance has passed; if the battery catches fire during the test, it means that the battery thermal abuse performance has failed.
[0126] (3) Constant current charging ratio: A fresh battery is first discharged at 0.2C to the lower limit voltage, then charged at 4C constant current to the upper limit voltage, and then charged to full charge at constant voltage. The constant current process charging capacity 1 and total charging capacity 2 of the battery are recorded. The constant current charging ratio is the charging capacity 1 divided by the total charging capacity 2.
[0127] (4) Lithium deposition: At 25°C, the battery was fully charged at 4C and discharged at 0.7C, repeated 20 times, and then the lithium ions were charged, and then the negative electrode was disassembled and the lithium deposition on the surface of the negative electrode was observed. Among them, the area of lithium deposition on the surface of the negative electrode is less than 10%, which is considered to be slight lithium deposition, the area of lithium deposition on the surface of the negative electrode is 10% to 50%, which is considered to be moderate lithium deposition, and the area of lithium deposition on the surface of the negative electrode is greater than 50%, which is considered to be severe lithium deposition.
[0128] (5) Energy density test: The battery is charged to 4.5V at a constant current of 0.7C, then charged to 0.05C at a constant voltage, left to stand for 10 minutes, and discharged to 3.0V at 0.2C to obtain the discharge capacity. The discharge capacity is taken as the nominal capacity. The energy of the battery is the nominal capacity multiplied by the average discharge voltage. The energy density of the battery is the energy of the battery divided by the volume of the battery.
[0129] The results of the above test data are shown in Table 3.
[0130] Table 3
[0131]
[0132]
[0133] From the above data, it can be seen that the presence of the first element, the second element and the third element can improve the constant current charging ratio of the battery, reduce the cycle expansion, and improve the thermal abuse performance of the battery. In addition, after the primary particles are treated with gas phase modification, the performance of the battery can also be improved to a certain extent.
[0134] At the same time, appropriate secondary particle size and primary particle size as well as appropriate proportions are beneficial to improving battery performance, can significantly reduce battery cycle expansion, maintain battery fast charging performance while improving battery thermal abuse performance.
[0135] In addition, different types of the first element to the third element will also affect the performance of the battery. Using appropriate types of the first element to the third element can improve the thermal abuse performance and cycle performance of the battery to a certain extent.
[0136] It should be noted that, in this article, the terms "comprise", "include" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be pointed out that the scope of the method and device in the embodiment of the present invention is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.
[0137] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A graphite negative electrode material, characterized in that: The graphite negative electrode material comprises primary particles and secondary particles comprising a coating layer; The surface of the primary particle contains oxygen-containing functional groups, the oxygen-containing functional groups include C=O, COO- and CO single-bond functional groups, and the total proportion of C=O functional groups and COO- functional groups in the oxygen-containing functional groups is greater than the proportion of CO single-bond functional groups; the coating layer contains a first element, a second element and a third element, the first element includes at least two of B, P, N, F and S, the second element is a transition metal, and the third element is an alkali metal and / or an alkaline earth metal; The graphite negative electrode material satisfies 0.01≤α / m≤0.1 and 0.5≤100*β*η / m≤10; Wherein, m is the mass content of carbon element in the graphite negative electrode material, in wt%; α, β and η are the mass contents of the first element, the second element and the third element in the graphite negative electrode material, in wt%; 6≤X1d1+X2d2≤12.6; wherein X1 and X2 are the mass contents of secondary particles and primary particles in the graphite negative electrode material, respectively; d1 and d2 are the median particle sizes of secondary particles and primary particles, respectively, in μm.
2. The graphite negative electrode material according to claim 1, characterized in that m ≥ 75; and / or 0<α≤9; and / or 0<β≤4; and / or 0<η≤3.
3. The graphite negative electrode material according to claim 1 or 2, characterized in that: In the primary particles, the mass content of O element is 5wt%-7wt%.
4. The graphite negative electrode material according to any one of claims 1 to 3, characterized in that: The first element comprises F and S. Preferably, in the graphite negative electrode material, the content of F is less than 5wt%, and the content of S is less than 4wt%; and / or The second element comprises at least one of Ti, Mn, Fe, Co, Ni and Cr, preferably Ti; and / or The third element includes at least one of Li, Ca and Na, and preferably includes Ca.
5. The graphite negative electrode material according to any one of claims 1 to 4, characterized in that: X1≥X2; preferably, 50%≤X1≤80%, 20%≤X2≤50%; and / or d1>d2.
6. The graphite negative electrode material according to any one of claims 1 to 5, characterized in that: The mass content of the coating layer in the graphite negative electrode material is W, and satisfies 0.4%≤W≤2.5%.
7. The graphite negative electrode material according to any one of claims 1 to 6, characterized in that: d is the median particle size of the graphite negative electrode material, in μm, 8≤d≤13.
8. The graphite negative electrode material according to any one of claims 1 to 7, characterized in that: In the button half-cell test, the capacity of the graphite negative electrode material when delithiation is to 0.3V is q1, the capacity when delithiation is to 0.85V is q2, and the capacity when delithiation is to 1.5V is q3, all in units of mA·h, and q1, q2 and q3 satisfy 0.04<(q3-q2) / (q3-q1)<0.
3.
9. A negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector, wherein the negative electrode active material layer comprises the graphite negative electrode material according to any one of claims 1 to 8; Preferably, the full charge extension rate of the negative electrode sheet is satisfy Preferably, the negative electrode OI value is and More preferably, the negative electrode sheet satisfies 10. A battery, characterized in that: The battery comprises the graphite negative electrode material according to any one of claims 1 to 8 and / or the negative electrode sheet according to claim 9.
Citation Information
Patent Citations
Negative plate, preparation method of negative plate and device using negative plate
CN116682941A
Graphite negative electrode material for stabilizing sulfide solid-state battery and preparation method of graphite negative electrode material
CN117673350A
Stabilized (partly) lithiated graphite materials, processes for their production and use for lithium batteries
DE102015202612A1
Negative electrode plate, electrochemical energy storage apparatus and electronic apparatus
US20230402603A1
